Sonographic Weight Estimation in Small-for-Gestational-Age Fetuses - Dammer, U.; Raabe, E.; Kehl, Sven; Schmid, M.; Mayr, Andreas; Schild, R. L.; Beckmann, Matthias; Faschingbauer, Florian (Ultraschall in der Medizin, 2015)
Purpose: To determine the accuracy of sonographic weight estimation (WE) for small-for-gestational-age (SGA) fetuses, and to further differentiate the evaluation between symmetric and asymmetric SGA fetuses. Materials and Methods: The accuracy of WE in SGA fetuses (n = 898) was evaluated using 14 sonographic models and was further differentiated between symmetric (n = 750) and asymmetric (n = 148) SGA fetuses. SGA fetuses were considered to be asymmetric with a head circumference to abdominal circumference ratio above the 95th percentile. The accuracy of the different formulas was compared using means of percentage errors (MPE), medians of absolute percentage errors (MAPE), and proportions of estimates within 10 % of actual birth weight. Results: Results for the subgroup of asymmetric SGA fetuses differed significantly from the subgroup of symmetric SGA fetuses. MPE values were closer to zero with most of the formulas in the asymmetric SGA group. Apart from the Siemer, Shepard, Merz and Warsof equations, all formulas showed an underestimation of fetal weight in asymmetric SGA fetuses. In contrast, in the symmetric SGA group, all of the formulas commonly used for fetuses in a normal weight range showed a systematic overestimation of fetal weight. Overall the best accuracy was achieved by using the Sabbagha equation (MPE 1.7 %; SD 9.0 %; MAPE: 6.0). Conclusion: An accurate WE in SGA fetuses is feasible using the Sabbagha formula. However, one has to be aware of the significant differences in WE between symmetric and asymmetric SGA fetuses.
EVALuna2:5471